Pengaruh Customer Satisfaction, e-service Quality, dan Trust terhadap e-wom Tokopedia di Indonesia - Hananto, Brian Alvin; Indrawan, Indrawan (Master of Management Diponegoro University, 2023)
This study aims to see the effect of customer satisfaction, e-service quality, and trust towards e-wom using Tokopedia as the research’s object. For this research, data is collected using an online questionnaire. The number of respondents for this research is 133. For data analysis, the author uses PLS-SEM using SmartPLS. This research results show that customer satisfaction and trust positively affect E-Wom, while E-service quality does not positively affect E-Wom.